Bioethanol production from mixed lignocellulosic substrates using cellulolytic termite gut bacteria and yeast - Oke, M.A.; Philip, K.; Ajam, N. (2013)
Energy insecurity and global warming associated with use of fossil fuels have led to intense efforts towards sustainable production of biofuels such as bioethanol. Utilization of biomass for the production of biofuels has been fraught with challenges such as fluctuating feedstock supply, high cost of feedstock handling, and other logistic problems. Most studies on lignocellulosic ethanol production have been based on single biomass feedstocks. Mixed biomass feedstock approach to the utilization of lignocellulosic biomass for ethanol production has the potential to overcome the challenges of biomass utilization, positively improve the bioethanol production process and generally boost the biorefinery concept. Oil palm biomass and wood wastes account for the greater portion of wastes generated annually in Malaysia and their accumulation is a serious environmental problem. This study aims to investigate the potential of mixed lignocellulosic biomass (oil palm frond and saw dust) as substrate for bioethanol production. Cellulolytic bacteria have been isolated from the gut of dry wood termites collected from infested wood. Screening of the isolates for cellulase production using cellulose hydrolytic capacity values on CMC agar plates and identification of the isolates